PELAKSANAAN PERJANJIAN BAGI HASIL MUZARA’AH DI JORONG SAWAH KAREH NAGARI BALIMBING MENURUT FIKIH MUAMALAH - Nini Zulhanif; Afrian Raus (Jurnal Integrasi Ilmu Syariah (Jisrah), 2021)
This paper examines the practice of implementing the Muzara'ah contract agreement in Jorong Sawah Kareh Nagari Balimbing. The purpose of this article is to find out and explain the practice of implementing the Muzara'ah contract in Jorong Sawah Kareh Nagari Balimbing in terms of three aspects, namely the implementation time limit, the form of profit sharing and ownership status according to Muamalah Fiqh. The results of the field study with data obtained from five groups of residents who carried out this muza'raah collaboration, the results obtained were that first; in terms of time limits, there is an implementation of the agreement that is not in accordance with the fiqh muamalah theory because when two groups cooperate and one of the parties dies, the muzara'ah agreement does not end. Second; in terms of profit-sharing, there are still cultivators who take the share of the land that should have been when one group that made the agreement dies, the contract and profit-sharing also end. However, the reality on the ground is that cultivators are still taking produce from the land. This is not in accordance with the concept of sharing the results of muzara'ah, unless it is then carried out with the concept of profit sharing on the basis of consensual agreement between the heirs of the land owner and the cultivators in the future. Third; viewed from the case of the concept of ownership status, land in the form of this cooperation belongs to imperfect property because land ownership is only in terms of the use of the object or its benefits. However, in practice there are groups who when the first party (land owner) dies and there is no stipulation on the expiration date of the muzara'ah in the agreement, assumes that he is the owner of the plant and still benefits from the land.